2D MXene nanosheets enable small-sulfur electrodes to be flexible for lithium–sulfur batteries. Issue 17 (15th April 2019) - Zhao, Qian; Zhu, Qizhen; Miao, Jiawei; Zhang, Peng; Xu, Bin
Abstract : A flexible small-sulfur electrode with MXene as a conductive binder and flexible backbone is constructed combining good flexibility, stable cycling and good rate performance. Abstract : Lithium–sulfur batteries are one of the most promising energy storage devices with high energy density, but their practical application is hindered by the serious capacity fading due to the shuttle effect resulting from the migration of polysulifdes during charge–discharge. Using small sulfur molecules (S2–4 ), in place of conventional cyclo-S8, as cathode materials is an efficient method to fundamentally eradicate the shuttle effect. To satisfy the demands of flexible electronic devices, in this paper, two-dimensional (2D) MXene nanosheets were used as a conductive binder and flexible backbone to combine with the S2–4 /carbon composite, fabricating a flexible small-sulfur electrode for lithium–sulfur batteries. The 2D MXene nanosheets with excellent conductivity can not only provide flexibility for the electrode, but also construct a conductive network for fast charge transfer. As a result, the flexible S2–4 electrode exhibits superior electrochemical performance, which has a capacity of 1029.7 mA h g −1 at 0.1 C and maintains 946.7 mA h g −1 after 200 cycles with 91.9% retention. Besides, a capacity of 502.3 mA h g −1 is obtained at 2 C current density. This electrode is promising for flexible lithium–sulfur batteries, and the application of MXene as a conductive binder and flexible backbone in lithium–sulfur batteries offers an effective method to achieve both flexibility and high performance.